Prognóstico de pacientes pediátricos com leucemia mieloide aguda - Hoch, Rosméri Elaine Essy (2020)
Acute Myeloid Leukemia (AML) is a highly aggressive disease in children and teenagers, affecting immature myeloid progenitor cells in the bone marrow. The prognosis of AML depends on a number of factors, such as: the leukemia subtype, the patient's age, changes in laboratory tests of peripheral blood and bone marrow, molecular and cytogenetic changes. However, in addition to these factors, many other epidemiological, clinical, laboratory, and genetic characteristics can influence the occurrence of refractory disease and disease recurrence. Thus, this study aimed to characterize the prognostic factors of pediatric patients; especially those related to refractory and post-recurrent AML disease, who received treatment at the Santa Maria University Hospital, a reference in the central region of the state of Rio Grande do Sul in pediatric oncology hematology, from January 2008 to December 2019. This was a retrospective cohort study, with an analysis of medical records from the Medical Archive Service. 51 children and teenagers were selected for the study, diagnosed and treated uniformly, divided into two groups: with complete remission of the disease 64.7% (n = 33) and with relapse of the disease or refractory disease 35.5% (n = 18). The two groups were homogeneous in relation to demographic data and clinical symptoms. The predominant profile was male children, white and aged from 1 to 10 years old, 70.8% (n = 17). As for the home, the greatest origin of patients was from the southwest region, 35.3% (n = 18). The main symptoms presented at diagnosis were: bleeding 52.9% (n = 27), fever 47.1% (n = 24) and asthenia 47.1% (n = 24). The most common subtype according to FAB (French-American-British) criteria was LMA M3 with 37.3% (n = 19); the highest rate of recurrence at AML M0 60.0% (n = 3/5). The hematological parameters of children with complete remission and those who had recurrence did not show a statistical difference between the groups. Genetic abnormalities t (15; 17); t (8; 21) were expressive, however both have a favorable prognosis. The FLT3-ITD gene mutation was the most prevalent and did not influence the prognosis. When comparing the antigen expression profile among children with AML remission, a greater expression of the granulocytic marker CD13 was observed (p = 0.022). Children with AML recurrence had a higher percentage of expression of the CD36 marker (p = 0.010) and of the abnormal expression markers CD4 (p = 0.006), CD7 (p = 0.008) and CD22 (p = 0.010). The most used treatment protocol was LMAIO 97 in 56.86% of cases (n = 29); in AML M3, the use of all-trans-retinoic acid (ATRA) was the option of choice in all cases (n = 19). The median overall survival (SG) was 68.7% at 2 years and the event-free survival (SLE) was 59.5%. According to the AML subtype (AML M3 and other types), the log-rank test (Mantel-Cox), p = 0.012, showed a significant difference. For patients with AML M3, SG at 2 months was 88.9% and for other types of AML, SG was 53.6%. There was also a significant difference in the SLE according to the log-rank test (Mantel-Cox), p = 0.003. The SLE for AML M3 was 88.9% up to 2 years (6 months, 1 year, and 2 years) and for patients with other types of AML, at 2 years of 30.6%. Death occurred mainly due to treatment, attributing infections (septicemia) as responsible. Our results showed the importance of analyzing demographic characteristics, clinical parameters, and laboratory tests, especially positive immunophenotypic markers of myeloid and lymphoid lineage in the outcome of AML to establish a reliable prognosis.